Penyelidikan Dan Penyidikan Dalam Perkara Pidana - Leasa, Cynthia Cornelia; Adam, Sherly; Hattu, Jacob (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Criminal law enforcement in Indonesia has started from a short but long and long time, at least it can be seen from the enactment of law number 8 of 1981 concernig the Criminal Procedure Code. Police in carrying out their duties as law enforcement officers must be based on law number 2 of 2002 Indonesian National Police.Purposes of the Research: Analyze and discuss the legal reasons reports in criminal cases and the legal consequences if a reported criminal case is not processed.Methods of the Research: This study uses a normative juridical research method because it uses a literature study that adheres to the juridical aspects with the types of statutory approaches, conceptual approaches, and case approaches.Results of the Research: The results of the study show that regulations regarding reports that can be rejected by the police have not been clearly regulated, only sanctions related to the police code of ethics are provided so that many people feel unfairly related to what yhe police have dne in terms of rejecting reports for reasons that are not clear on the law. Investigationsinto criminal cases have also not been fully carried out because many investigators are less professional. If it results of the investigations of the report cannot meet the evidence, the investigator can stop the investigation being carried out.